Twenty‐first century adaptive teaching and individualized learning operationalized as specific blends of student‐centered instructional events: A systematic review and meta‐analysis - Bernard, Robert M.; Borokhovski, Eugene; Schmid, Richard F.; Waddington, David I.; Pickup, David I. (Campbell systematic review, 2019)
Teaching methods that individualize and adapt instructional conditions to K-12 learners' needs, abilities, and interests help improve learning achievement. The most important variables are the teacher's role in the classroom as a guide and mentor and the adaptability of learning activities and materials. This Campbell systematic review assesses the overall impact on student achievement of processes and methods that are more student-centered versus less student-centered. It also considers the strength of student-centered practices in four teaching domains: (1) Flexibility: Degree to which students can contribute to course design, selecting study materials, and stating learning objectives; (2) Pacing of instruction: Students can decide how fast to progress through course content and whether this progression is linear or iterative; (3) Teacher's role: Ranging from authority figure and sole source of information, to teacher as equal partner in the learning process; and (4) Adaptability: Degrees of manipulating learning environments, materials, and activities to make them more student-centered. This review presents evidence from 299 studies (covering 43,175 students in a formal school setting) yielding 365 estimates of the impact of teaching practices. The studies spanned the period 2000-2017 and were mostly carried out in the United States, Europe, and Australia. This review confirms previous research on the effectiveness of student-centered and active learning. It goes further in suggesting the teacher's role promotes effective student-centered learning, and excessive student control over pacing appears to inhibit it.